2016
DOI: 10.1111/cmi.12693
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-The ultimate weapon to battle infectious diseases?

Abstract: Infectious diseases are a leading cause of death worldwide. Novel therapeutics are urgently required to treat multidrug-resistant organisms such as Mycobacterium tuberculosis and to mitigate morbidity and mortality caused by acute infections such as malaria and dengue fever virus as well as chronic infections such as human immunodeficiency virus-1 and hepatitis B virus. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system, which has revolutionized bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 96 publications
(142 reference statements)
0
35
0
Order By: Relevance
“…CRISPR technology has gained much attention for its gene editing abilities, mainly in mammalian cells (193,194). However, there has been considerable research into the use of CRISPR for the treatment of infectious diseases (195). Seminal research by Bikard et al demonstrated the potential to use CRISPR/Cas9 in targeting staphylococcal infection by targeting the methicillin resistance gene in S. aureus, making a MRSA isolate susceptible to methicillin once again (196).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…CRISPR technology has gained much attention for its gene editing abilities, mainly in mammalian cells (193,194). However, there has been considerable research into the use of CRISPR for the treatment of infectious diseases (195). Seminal research by Bikard et al demonstrated the potential to use CRISPR/Cas9 in targeting staphylococcal infection by targeting the methicillin resistance gene in S. aureus, making a MRSA isolate susceptible to methicillin once again (196).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Understanding mechanisms by which bacteria, viruses, fungi, and parasites induce human disease is essential to guide optimal clinical care and rational design of targeted therapies and vaccines. CRISPR-Cas9-based gene editing has been used across diverse pathogens to inform gene and protein contributions to molecular pathogenesis (28). Winter et al employed a CRISPR-Cas9 sgRNA library to elucidate the mechanism by which ␣-hemolysin, a Staphylococcus aureus virulence factor, induces cytotoxicity (29).…”
Section: Infectious Disease Applicationsmentioning
confidence: 99%
“…The complex is capable of cleaving the target DNA sequence known as the photospacer guide sequence and the 5′‐NGG‐3′ sequence known as the protospacer adjacent motif (PAM) . This technique can be used in different pathogens such as bacteria, viruses, and parasites to lessen virulence . The use of this system could increase the efficiency of vaccine antigens against infectious diseases and that of cancer immunotherapy in the host .…”
Section: Strategies For Modulating Mirna Function Against Infectious mentioning
confidence: 99%